KAJIAN POTENSI PRODUKSI PADI DAERAH IRIGASI BANDAR SIDORAS DI KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG (The Study of Rice Production Potential in Bandar Sidoras Irrigation Fields in Percut Sei Tuan District Deli Serdang Regency) - Isti Mauladina; Sumono Sumono; Sulastri Panggabean (Jurnal Rekayasa Pangan dan Pertanian, 2017)
ABSTRACT Percut Sei Tuan District as the largest centre of rice production in Deli Serdang Regency, must be studied its rice field irrigation system to hold out and increase rice production. The purpose of this research was to study the rice production potential in Bandar Sidoras irrigation fields in Percut Sei Tuan district Deli Serdang regency in achieving the maximum level of rice production based on sun  radiation level, time to grow rice, and rice variety. This research was also studied the ratio between irrigation field and crops field, and reliability of existing irrigation networks. In the period of 2009-2013, the results indicated that the irrigation network reliability was good enough. The average value of the actual productivity of rice was 5,63 ton/ha, the average ratio between irrigation field and crops field was 2,98 and the rice production target was 64,09%. Keyword: rice, production target, production potential, irrigation network. ABSTRAK Kecamatan Percut Sei Tuan sebagai daerah penghasil produksi padi terbesar di Kabupaten Deli Serdang, perlu dikaji jaringan irigasinya yang menjadi sumber air untuk meningkatkan produksi padi. Penelitian ini bertujuan untuk mengkaji potensi produksi padi Daerah Irigasi Bandar Sidoras di Kecamatan Percut Sei Tuan Kabupaten Deli Serdang  dalam aras pencapaian produksi padi yang maksimal, berdasarkan tingkat radiasi matahari, lama waktu pertumbuhan tanaman padi, serta varietas padi yang ditanam. Penelitian ini juga mengkaji nisbah luas lahan panen dengan luas lahan beririgasi, dan keandalan jaringan irigasi. Dalam kurun waktu 2009-2013 diperoleh hasil bahwa keandalan jaringan irigasi terpenuhi. Rata-rata nilai produktivitas aktual padi 5,63 ton/ha, rata-rata nilai nisbah luas panen dengan luas lahan beririgasi 2,98 dan rata-rata nilai aras pencapaian produksi padi 64,09%. Kata Kunci: padi, aras produksi, potensi produksi, jaringan irigasi.